Composite heterojunction photocatalytic coating as well as preparation method and application thereof

By using a composite photocatalyst in heterojunction photocatalytic coatings and utilizing the synergistic effect of BiOCl and copper sulfate pentahydrate, the problem of insufficient formaldehyde degradation performance of existing coatings is solved and the catalytic efficiency is significantly improved.

CN119320580APending Publication Date: 2025-01-17GUOKE XIANCAI (HEFEI) TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411438647.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The degradation performance of existing heterojunction photocatalytic coatings to formaldehyde needs to be improved in practical applications.

Method used

Composite heterojunction photocatalytic coatings are used, including photocatalysts, film-forming agents, pigments and fillers, dispersants, wetting agents, thickeners, defoaming agents, bactericides and water, and are prepared through specific preparation methods. Obtaining the photocatalyst includes the steps of stirring and mixing microspherical BiOCl and copper sulfate pentahydrate solution, adding NaOH and ascorbic acid solution and then precipitating, washing and drying.

Benefits of technology

It improves the formaldehyde degradation performance of the coating. BiOCl generates abundant surface oxygen vacancies under light induction, promotes visible light absorption and carrier separation, and enhances the photocatalytic efficiency of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320580A_ABST
    Figure CN119320580A_ABST
Patent Text Reader

Abstract

The invention discloses a composite heterojunction photocatalytic coating as well as a preparation method and application thereof, and relates to the technical field of environment-friendly coatings for buildings. According to the composite heterojunction photocatalytic coating and the preparation method and application thereof, BiOC1 generates rich surface oxygen vacancies under light induction, impurity energy levels can be formed in band gaps, the visible light absorption capacity is promoted, photo-induced electrons can be captured and promoted to be transferred to the surface of a photocatalyst, and therefore photon-generated carrier recombination is inhibited, and the photocatalytic performance of the photocatalyst is improved. Meanwhile, surface oxygen vacancies generated by light induction can efficiently promote hole (h < + >) oxidation and generate more active species such as superoxide free radicals O < 2-> to promote degradation of organic pollutants, and heterojunction is constructed by using Cu0, so that the light absorption range of BiOCl can be widened, the photocatalytic efficiency of the catalyst is further improved, and the formaldehyde degradation performance of the coating is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of environmentally friendly architectural coatings, and in particular to a composite heterojunction photocatalytic coating, a preparation method thereof and an application thereof. Background Art

[0002] Heterojunction photocatalytic coating is a functional coating that can catalyze reactions under the irradiation of light of a specific wavelength. It combines heterojunction technology and photocatalytic principles, and has the characteristics of self-cleaning, sterilization, deodorization, environmental protection, high efficiency, weather resistance and wide application. This coating can decompose organic matter and pollutants in the air under light conditions by generating free radicals and active oxygen, keep the coating surface clean and reduce the frequency of cleaning. At the same time, it can also decompose microorganisms such as bacteria and mold to improve indoor air quality and reduce the risk of disease transmission. Heterojunction photocatalytic coating itself is non-toxic and harmless, and the process of decomposing pollutants does not produce harmful substances. It is an environmentally friendly coating.

[0003] The Chinese patent with publication number CN115746632A discloses a photocatalytic coating for degrading VOCs and its preparation method. The coating contains film-forming substances, pigments and fillers, dispersants, stabilizers, wetting agents, defoamers, etc. The photocatalytic coating contains the photocatalyst TiO2-Bi 12 O 17 Cl x Br2-x (0<x<2). The TiO2 photocatalytic material was modified by combining three modification strategies: heterojunction, solid solution and dehalogenation. Under the irradiation of visible light, the photocatalytic coating can achieve a maximum formaldehyde removal efficiency of 85.1% in 24 hours and a maximum NO2 removal rate of 78.7% in 12 hours. The visible light catalytic performance of the photocatalyst is improved, making the TiO2-Bi 12 O 17 Cl x Br2-x (0<x<2) photocatalyst coating can degrade VOC gas in the air under the irradiation of visible light. The above-mentioned prior art solution has the problem that the degradation performance of the coating on formaldehyde needs to be further improved during the actual application process; therefore, the present invention provides a composite heterojunction photocatalytic coating and its preparation method and application to solve the above-mentioned problem. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a composite heterojunction photocatalytic coating and a preparation method and application thereof, which solve the problems mentioned in the above background technology.

[0005] To achieve the above purpose, the present invention is implemented by the following technical scheme: a composite heterojunction photocatalytic coating, comprising the following components in parts by weight: 50-100 parts of photocatalyst, 80-120 parts of film-forming agent, 200-500 parts of pigment filler, 5-10 parts of dispersant, 1-3 parts of wetting agent, 10-20 parts of thickener, 1-3 parts of defoamer, 3-6 parts of bactericide, and 200-300 parts of water;

[0006] Wherein, the preparation method of the photocatalyst is:

[0007] Ⅰ. Stir and mix the microspherical BiOCl with copper sulfate pentahydrate solution;

[0008] Ⅱ. Add 3 mol / L NaOH solution and 1.2 mol / L ascorbic acid solution to the mixed solution of Ⅰ in sequence, and continue stirring for 30 to 40 minutes to produce a precipitate;

[0009] Ⅲ. Wash the precipitate alternately with anhydrous ethanol and distilled water;

[0010] IV. Place in a drying oven at 60-65°C and dry for 4-6 hours to obtain a photocatalyst;

[0011] The weight proportions of the components in the photocatalyst are: 30-45 parts of microspherical BiOCl, 15-18 parts of copper sulfate pentahydrate solution, 2-3 parts of NaOH solution and 2.4-3.2 parts of ascorbic acid solution.

[0012] Preferably, the film-forming agent is styrene acrylic emulsion, the pigment filler is a mixture of barium sulfate and kaolin, the dispersant is sodium hexapolyphosphate, the wetting agent is polyoxyethylene alkylphenol ether, the thickener is hydroxypropyl methylcellulose, the defoamer is polydimethylsiloxane, and the bactericide is isothiazolinone.

[0013] Preferably, in said Ⅰ, the specific preparation method of microspherical BiOCl is:

[0014] (1) mixing butyl titanate and furfural, pouring the mixture into anhydrous ethanol to obtain a mixed solution, and stirring the mixture at room temperature for 30 to 35 minutes;

[0015] (2) adding BiOCl nanoplates to the mixed solution of (1), heating to 180-200° C. and reacting for 12-14 hours to produce a precipitate;

[0016] (3) centrifuging and washing the precipitate with deionized water and anhydrous ethanol in sequence;

[0017] (4) The precipitate is then placed in a drying oven at 60-70°C and dried for 7-8 hours, and then ground into powder to obtain microspherical BiOCl.

[0018] Preferably, the mass ratio of butyl titanate, furfural and BiOCl nanoplates is 1:(1.8-2.1):(0.5-0.6).

[0019] Preferably, in (2), the preparation method of BiOCl nanoplate is:

[0020] S1. Pour Bi(NO3)3·5H2O into 20 mL of deionized water at room temperature for dispersion.

[0021] S2. Pour KCl into 20 mL of deionized water at room temperature and stir to dissolve;

[0022] S3, slowly add the solution prepared in S2 to the solution prepared in S1, and stir for 30 to 40 minutes;

[0023] S4, heating to 140-150°C for hydrothermal reaction, the reaction time is 8-10h;

[0024] S5. After the reaction is completed, the mixture is naturally cooled to room temperature and the product is centrifuged to obtain a precipitate;

[0025] S6. Wash the precipitate with ethanol and water in turn and then air-dry it to obtain BiOCl nanoparticles.

[0026] Preferably, the mass ratio of Bi(NO3)3·5H2O to KCl is 1:1; in S6, the air-drying temperature is 50-60°C.

[0027] A method for preparing a composite heterojunction photocatalytic coating specifically comprises the following preparation steps: weighing various raw materials and mixing them evenly to obtain the composite heterojunction photocatalytic coating.

[0028] The invention discloses an application of a composite heterojunction photocatalytic coating for indoor formaldehyde degradation and outdoor nitrogen oxide degradation.

[0029] Beneficial Effects

[0030] The present invention provides a composite heterojunction photocatalytic coating and a preparation method and application thereof. Compared with the prior art, the composite heterojunction photocatalytic coating and a preparation method and application thereof have the following beneficial effects: the composite heterojunction photocatalytic coating and a preparation method and application thereof, BiOC1 generates abundant surface oxygen vacancies under light induction, which can not only form impurity energy levels in the band gap and promote visible light absorption capacity, but also capture photogenerated electrons and promote their transfer to the photocatalyst surface, thereby inhibiting the recombination of photogenerated carriers. At the same time, the surface oxygen vacancies generated by light induction can efficiently promote holes (h + ) oxidation and production of more superoxide radicals O2 -Active species such as BiOCl can be used to promote the degradation of organic pollutants, and by using Cu0 to construct a heterojunction, the absorption range of BiOCl to light can be broadened, thereby improving the photocatalytic efficiency of the catalyst and improving the degradation performance of the coating on formaldehyde. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A comparison chart of formaldehyde degradation effects provided by a composite heterojunction photocatalytic coating and a preparation method and application thereof of the present invention;

[0032] Figure 2 The photocatalyst SEM image is provided for a composite heterojunction photocatalytic coating and a preparation method and application thereof of the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] A method for preparing a composite heterojunction photocatalytic coating comprises the following steps:

[0036] Step 1: Pour 2 g of Bi(NO3)3·5H2O into 20 mL of deionized water at room temperature for dispersion to obtain a mixed solution 1; pour 2 g of KCl into 20 mL of deionized water for stirring and dissolving to obtain a mixed solution 2; slowly drop the mixed solution 2 into the mixed solution 1; stir for 30 min; heat to 140°C for hydrothermal reaction; the reaction time is 8 h; after the reaction is completed, naturally cool to room temperature; centrifuge the product to obtain a precipitate; wash the precipitate with ethanol and water in turn; and air-dry it at 50°C to obtain a BiOCl nanoplate;

[0037] Step 2: 5 g of butyl titanate and 9 g of furfural were mixed and poured into 60 mL of anhydrous ethanol to obtain a mixed solution. After stirring at room temperature for 30 min, 3 g of BiOCl nanoplate was added, and the mixture was heated to 180 ° C. and reacted for 12 h to produce a precipitate. The precipitate was centrifuged and washed with deionized water and anhydrous ethanol in sequence, and then the precipitate was placed in a drying oven at 60 ° C. and dried for 7 h and then ground into powder to obtain microspherical BiOCl;

[0038] Step 3: 30 g of microspherical BiOCl was stirred and mixed with 18 g of copper sulfate pentahydrate solution, and then 3 g of 3 mol / L NaOH solution and 3.2 g of 1.2 mol / L ascorbic acid solution were added in sequence, and the stirring was continued for 30 min to produce a precipitate. The precipitate was alternately washed with anhydrous ethanol and distilled water, and then placed in a drying oven at 60 ° C for 4 h to obtain a photocatalyst;

[0039] Step 4. Weigh the raw materials: 50 g of photocatalyst, 120 g of styrene-acrylic emulsion, 500 g of a mixture of barium sulfate and kaolin, 10 g of sodium hexapolyphosphate, 3 g of polyoxyethylene alkylphenol ether, 20 g of hydroxypropyl methylcellulose, 3 g of polydimethylsiloxane, 6 g of isothiazolinone, and 300 g of water, and mix them evenly to obtain a composite heterojunction photocatalytic coating.

[0040] Example 2

[0041] A method for preparing a composite heterojunction photocatalytic coating comprises the following steps:

[0042] Step 1: Pour 2 g of Bi(NO3)3·5H2O into 20 mL of deionized water at room temperature for dispersion to obtain a mixed solution 1; pour 2 g of KCl into 20 mL of deionized water for stirring and dissolving to obtain a mixed solution 2; slowly drop the mixed solution 2 into the mixed solution 1; stir for 35 min; heat to 145°C for hydrothermal reaction; the reaction time is 9 h; after the reaction is completed, naturally cool to room temperature; centrifuge the product to obtain a precipitate; wash the precipitate with ethanol and water in turn; and air-dry it at 55°C to obtain a BiOCl nanoplate;

[0043] Step 2: 5 g of butyl titanate and 10 g of furfural were mixed and poured into 60 mL of anhydrous ethanol to obtain a mixed solution. After stirring at room temperature for 35 min, 2.8 g of BiOCl nanoplate was added, and the mixture was heated to 190 ° C. and reacted for 13 h to produce a precipitate. The precipitate was centrifuged and washed with deionized water and anhydrous ethanol in sequence, and then the precipitate was placed in a drying oven at 65 ° C. and dried for 7 h and then ground into powder to obtain microspherical BiOCl;

[0044] Step 3: 40 g of microspherical BiOCl was stirred and mixed with 16 g of copper sulfate pentahydrate solution, and then 2.5 g of 3 mol / L NaOH solution and 3 g of 1.2 mol / L ascorbic acid solution were added in sequence, and the stirring was continued for 35 min to produce a precipitate. The precipitate was washed alternately with anhydrous ethanol and distilled water, and then placed in a drying oven at 65 ° C. for 5 h to obtain a photocatalyst;

[0045] Step 4. Weigh the raw materials: 75g of photocatalyst, 100g of styrene-acrylic emulsion, 350g of a mixture of barium sulfate and kaolin, 8g of sodium hexapolyphosphate, 2g of polyoxyethylene alkylphenol ether, 15g of hydroxypropyl methylcellulose, 2g of polydimethylsiloxane, 5g of isothiazolinone, and 250g of water, and mix them evenly to obtain a composite heterojunction photocatalytic coating.

[0046] Example 3

[0047] A method for preparing a composite heterojunction photocatalytic coating comprises the following steps:

[0048] Step 1: Pour 2 g of Bi(NO3)3·5H2O into 20 mL of deionized water at room temperature for dispersion to obtain a mixed solution 1; pour 2 g of KCl into 20 mL of deionized water for stirring and dissolving to obtain a mixed solution 2; slowly drop the mixed solution 2 into the mixed solution 1; stir for 40 min; heat to 150° C. for hydrothermal reaction; the reaction time is 10 h; after the reaction is completed, naturally cool to room temperature; centrifuge the product to obtain a precipitate; wash the precipitate with ethanol and water in turn; and air-dry it at 60° C. to obtain a BiOCl nanoplate;

[0049] Step 2: 5 g of butyl titanate and 10.5 g of furfural were mixed and poured into 60 mL of anhydrous ethanol to obtain a mixed solution. After stirring at room temperature for 35 min, 2.5 of BiOCl nanoplates were added, and the mixture was heated to 200 ° C for 14 h to generate a precipitate. The precipitate was centrifuged and washed with deionized water and anhydrous ethanol in turn. The precipitate was placed in a drying oven at 70 ° C for 8 h and then ground into powder to obtain microspherical BiOCl;

[0050] Step 3: 45 g of microspherical BiOCl and 15 g of copper sulfate pentahydrate solution were stirred and mixed, and then 2 g of 3 mol / L NaOH solution and 2.4 g of 1.2 mol / L ascorbic acid solution were added in sequence, and the stirring was continued for 40 min to produce a precipitate. The precipitate was alternately washed with anhydrous ethanol and distilled water, and then placed in a drying oven at 65 ° C. for 6 h to obtain a photocatalyst;

[0051] Step 4. Weigh the raw materials: 100 g of photocatalyst, 80 g of styrene-acrylic emulsion, 200 g of a mixture of barium sulfate and kaolin, 5 g of sodium hexapolyphosphate, 1 g of polyoxyethylene alkylphenol ether, 10 g of hydroxypropyl methylcellulose, 1 g of polydimethylsiloxane, 3 g of isothiazolinone, and 200 g of water, and mix them evenly to obtain a composite heterojunction photocatalytic coating.

[0052] Comparative Example 1

[0053] A method for preparing a composite heterojunction photocatalytic coating comprises the following steps:

[0054] Step 1: 5 g of butyl titanate and 9 g of furfural were mixed and poured into 60 mL of anhydrous ethanol to obtain a mixed solution. After stirring at room temperature for 30 min, 3 g of BiOCl nanoplate was added, and the mixture was heated to 180 ° C. and reacted for 12 h to produce a precipitate. The precipitate was centrifuged and washed with deionized water and anhydrous ethanol in sequence. The precipitate was then placed in a drying oven at 60 ° C. and dried for 7 h and then ground into powder to obtain microspherical BiOCl;

[0055] Step 2: 30 g of microspherical BiOCl and 18 g of copper sulfate pentahydrate solution were stirred and mixed, and then 3 g of 3 mol / L NaOH solution and 3.2 g of 1.2 mol / L ascorbic acid solution were added in sequence, and the stirring was continued for 30 min to produce a precipitate. The precipitate was alternately washed with anhydrous ethanol and distilled water, and then placed in a drying oven at 60 ° C for 4 h to obtain a photocatalyst;

[0056] Step 3. Weigh the raw materials: 50 g of photocatalyst, 120 g of styrene-acrylic emulsion, 500 g of a mixture of barium sulfate and kaolin, 10 g of sodium hexapolyphosphate, 3 g of polyoxyethylene alkylphenol ether, 20 g of hydroxypropyl methylcellulose, 3 g of polydimethylsiloxane, 6 g of isothiazolinone, and 300 g of water, and mix them evenly to obtain a composite heterojunction photocatalytic coating.

[0057] Comparative Example 2

[0058] Step 1: 30 g of BiOCl nanoplates were stirred and mixed with 18 g of copper sulfate pentahydrate solution, and then 3 g of 3 mol / L NaOH solution and 3.2 g of 1.2 mol / L ascorbic acid solution were added in sequence, and the stirring was continued for 30 min to produce a precipitate. The precipitate was alternately washed with anhydrous ethanol and distilled water, and then placed in a drying oven at 60 ° C for 4 h to obtain a photocatalyst;

[0059] Step 2: Weigh the raw materials: 50 g of photocatalyst, 120 g of styrene-acrylic emulsion, 500 g of a mixture of barium sulfate and kaolin, 10 g of sodium hexapolyphosphate, 3 g of polyoxyethylene alkylphenol ether, 20 g of hydroxypropyl methylcellulose, 3 g of polydimethylsiloxane, 6 g of isothiazolinone, and 300 g of water, and mix them evenly to obtain a composite heterojunction photocatalytic coating.

[0060] Formaldehyde removal performance test: the coating was evenly applied on a glass sheet of 30cm×15cm in size, and placed in a photocatalytic test box after curing and curing. The light source was a 300W xenon lamp (CEL-HXF300), with a 420nm filter cutoff. The formaldehyde concentration in the test box was 5ppm. The ultraviolet light was turned on to degrade the formaldehyde. The degradation of formaldehyde gas was detected every 2 hours using gas chromatography. The gas chromatograph was Angilent-6890, and the total test time was 12 hours. The formaldehyde degradation rate was calculated as follows:

[0061]

[0062] Where, X is the formaldehyde degradation rate, %; C0 is the initial concentration of formaldehyde without light; C t is the formaldehyde concentration at illumination time t.

[0063] NO2 degradation performance test: refer to GB / T 39716-2020 for testing; take 15g of each coating and evenly apply it on a glass sheet of 30cm×15cm in size. After curing and curing, place it in a photocatalytic test box, pass standard air and NO2, and use a 300W xenon lamp (CEL-HXF300) for irradiation. The filter is cut off at 420nm, the standard air flow rate is 3.0L / min, the NO2 flow rate is 25mL / min, and the NO2 concentration is 500mg / m 3 The outlet of the reactor is connected to N0 x The analyzer was used, and the concentration of nitrogen oxides was sampled and tested every 2 hours and recorded; the results are shown in Table 1. The calculation formula for the NO2 degradation rate is:

[0064]

[0065] Where D is the degradation rate of NO2, %; ρ0 is the equilibrium concentration of NO2 without light; ρ t is the real-time concentration of NO2 after illumination.

[0066] Table 1

[0067]

[0068] As shown in Table 1 and Figure 1 As shown, the degradation rates of NO2 and formaldehyde by the coatings prepared in Examples 1-3 are significantly improved compared with those in Comparative Examples 1-2; this is because the microspherical BiOCl can utilize light energy to excite electrons and holes on the surface of the catalyst, thereby generating free radicals with strong oxidizing properties, which can react with pollutants and decompose them into harmless substances; and [Bi202] 2+The built-in electric field formed with the Cl element is helpful for the separation of photogenerated carriers, and the introduction of GuO can further promote this process. The interface effect between the two can form a channel that is conducive to carrier transmission, reduce carrier recombination, and thus improve the photocatalytic efficiency. Moreover, copper oxide and microspherical BiOCl have different redox potentials, and the synergistic effect between them may enhance the redox ability of the entire photocatalyst, allowing more photogenerated electrons and holes to participate in the photocatalytic reaction.

[0069] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

Claims

1. A composite heterojunction photocatalytic coating, characterized in that: The invention comprises the following components in parts by weight: 50-100 parts of photocatalyst, 80-120 parts of film-forming agent, 200-500 parts of pigment and filler, 5-10 parts of dispersant, 1-3 parts of wetting agent, 10-20 parts of thickener, 1-3 parts of defoaming agent, 3-6 parts of bactericide and 200-300 parts of water; Wherein, the preparation method of the photocatalyst is: Ⅰ. Stir and mix the microspherical BiOCl with copper sulfate pentahydrate solution; Ⅱ. Add 3 mol / L NaOH solution and 1.2 mol / L ascorbic acid solution to the mixed solution of Ⅰ in sequence, and continue stirring for 30 to 40 minutes to produce a precipitate; Ⅲ. Wash the precipitate alternately with anhydrous ethanol and distilled water; IV. Place in a drying oven at 60-65°C and dry for 4-6 hours to obtain a photocatalyst; The weight proportions of the components in the photocatalyst are: 30-45 parts of microspherical BiOCl, 15-18 parts of copper sulfate pentahydrate solution, 2-3 parts of NaOH solution and 2.4-3.2 parts of ascorbic acid solution.

2. The composite heterojunction photocatalytic coating according to claim 1, characterized in that: The film-forming agent is styrene acrylic emulsion, the pigment filler is a mixture of barium sulfate and kaolin, the dispersant is sodium hexapolyphosphate, the wetting agent is polyoxyethylene alkylphenol ether, the thickener is hydroxypropyl methylcellulose, the defoaming agent is polydimethylsiloxane, and the bactericide is isothiazolinone.

3. The composite heterojunction photocatalytic coating according to claim 1, characterized in that: In said Ⅰ, the specific preparation method of microspherical BiOCl is: (1) mixing butyl titanate and furfural, pouring the mixture into anhydrous ethanol to obtain a mixed solution, and stirring the mixture at room temperature for 30 to 35 minutes; (2) adding BiOCl nanoplates to the mixed solution of (1), heating to 180-200° C. and reacting for 12-14 hours to produce a precipitate; (3) centrifuging and washing the precipitate with deionized water and anhydrous ethanol in sequence; (4) The precipitate is then placed in a drying oven at 60-70°C and dried for 7-8 hours, and then ground into powder to obtain microspherical BiOCl.

4. The composite heterojunction photocatalytic coating according to claim 3, characterized in that: in, The mass ratio of butyl titanate, furfural and BiOCl nanoplate is 1:(1.8-2.1):(0.5-0.6).

5. The composite heterojunction photocatalytic coating according to claim 3, characterized in that: In (2), the preparation method of BiOCl nanoplate is: S1. Pour Bi(NO3)3·5H2O into 20 mL of deionized water at room temperature for dispersion. S2. Pour KCl into 20 mL of deionized water at room temperature and stir to dissolve; S3, slowly add the solution prepared in S2 to the solution prepared in S1, and stir for 30 to 40 minutes; S4, heating to 140-150°C for hydrothermal reaction, the reaction time is 8-10h; S5. After the reaction is completed, the mixture is naturally cooled to room temperature and the product is centrifuged to obtain a precipitate; S6. Wash the precipitate with ethanol and water in turn and then air-dry it to obtain a BiOCl nanoplate.

6. The composite heterojunction photocatalytic coating according to claim 5, characterized in that: The mass ratio of Bi(NO3)3·5H2O to KCl is 1:1; in S6, the air-drying temperature is 50-60°C.

7. A method for preparing the composite heterojunction photocatalytic coating according to claim 1, characterized in that: The method specifically comprises the following preparation steps: weighing various raw materials and mixing them evenly to obtain a composite heterojunction photocatalytic coating.

8. Use of the composite heterojunction photocatalytic coating as claimed in any one of claims 1 to 7 in the degradation of formaldehyde indoors and nitrogen oxides outdoors.

Citation Information

Patent Citations

  • Bismuth oxychloride loaded cuprous oxide photocatalyst and preparation method and application thereof

    CN113145139A